Rancang bangun Dua Sistem untuk Vakum dan Kompresi dalam Satu Alat yang Digunakan untuk Vacuum Infusion pada Laminasi Kapal Fiber - Aristi Hanifah Fauziyyah; Heroe Poernomo; Gaguk Suhardjito (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The method of working vacuum infusion in the shipyard in Indonesia has not beenmaximally. Due to the large number of equipment required, resulting in shipyard owners still usinghand lay-up methods in the process. But in fact the vacuum infunsion method has many advantagesamong lighter and stronger ships, from the cost-savings due to fewer labor costs, faster executiontime. In analyzing the above problems using several stages of research and testing. In this studyincludes the required specifications for the suction speed used in the vacuum pump. While in thetesting phase is in the test whether the compressor can function in vacuum and compression. Basedon the result of the final assignment study entitled the design of two systems for vacuum andcompression in a tool used for vacuum infusion in the fiber vessel lamination process resulted in thatthe compressor can be used for compression and vacuum but can not be used simultaneously shouldswitch between its use between vacuum and compression. While the pressure generated by thecompressor for vacuum infusion is - 0.077 bar.